Secukinumab-induced Crohn’s disease in a psoriasis patient: a case report highlighting paradoxical reactions to IL-17 inhibition - Dai, Huiling; Xu, Chenyi; Wang, Yehuang; Wu, Kunlan; Zhang, Yang; Ge, Hao; Wu, Yanlan (Frontiers in Immunology, 2025)
Secukinumab, a monoclonal antibody targeting interleukin-17A, is effective for treating moderate-to-severe plaque psoriasis but may induce paradoxical inflammatory bowel disease, particularly Crohn’s disease. We describe a 41-year-old male with a history of psoriasis who developed new-onset Crohn’s disease accompanied by a perianal abscess after prolonged secukinumab treatment. The patient experienced increased bowel movements and postoperative fever, and colonoscopy revealed diffuse colonic inflammation and deep ulcerations; histopathology confirmed chronic active enteritis with epithelioid granulomas. Infectious causes and other differential diagnoses were excluded. Treatment with corticosteroids and mesalamine led to symptom resolution and normalization of inflammatory markers. This case illustrates a rare but important adverse effect of IL-17A inhibition and emphasizes the dual role of IL-17A in promoting skin inflammation while maintaining intestinal homeostasis. Careful evaluation of gastrointestinal history and close monitoring during therapy are essential to prevent and manage potential intestinal complications.